Physical distancing reduced the incidence of influenza and supports a favorable impact on SARS-CoV-2 spread in Mexico - Efrén Murillo-Zamora; José Guzmán-Esquivel; Ramón Alberto Sánchez-Piña; Guillermo Cedeño-Laurent; Iván Delgado-Enciso; Oliver Mendoza-Cano (Journal of Infection in Developing Countries)
Introduction: Physical distancing preventive measures were implemented in Mexico as a response to the coronavirus disease 2019 (CoViD-19) pandemic. School closures occurred on March 16, 2020, in 10 out of 32 Mexican states, and one week later in the remaining states. Because the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the influenza virus have similar transmission mechanisms, we aimed to evaluate the impact of physical distancing on the incidence of influenza as a proxy of the impact on SARS-CoV-2 contagion.